The Implementation of Social Capital in the Management of Fisheries Cooperatives (Study at the Maya Rita Sentosa Cooperative Tondonggeu Village Nambo District Kendari City) - Vina Avriayanti Almunawar; La Ode Alwi; La Ode Kasno Arief (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Tondonggeu Town, Nambo Region, Kendari City is a waterfront area with bountiful potential for fisheries area. The only village in Nambo District with a Fisheries cooperative organisation known as Koperasi Maya Rita Sentosa is Tondonggeu Village. The Maya Rita Sentosa Cooperative's origins and continued existence are intriguing topics that researchers should investigate in greater depth. The goals of this study were the Maya Rita Sentosa Cooperative's implementation of management functions and the impact of social capital on management. The study was conducted between December 2021 and October 2022. The number of respondents, specifically all individuals from the helpful Maya Rita Sentosa, was 36. The research variables used are Cooperative Management (Planning, organising, directing, and supervising) and Social Capital (trust, network, social norms, and participation). Information investigation utilising Different Direct Relapses. With an average score of 12.43, the study demonstrates that the Maya Rita Sentosa Cooperative's social capital, including trust, network, social norms, and participation, is high. The Maya Rita Sentosa Cooperative's overall implementation of management functions, including Planning, organising, direction, and supervision, receives an average score of 12.85, placing it in the high category. From the consequences of numerous direct relapse tests, the impact of social capital factors such as trust, organisation, accepted practices, and interest in the administration of cooperatives shows that trust, organisation and normal practices have a massive impact. At the same time, the investment variable makes no difference. Important effect.